1959
DOI: 10.1039/jr9590001587
|View full text |Cite
|
Sign up to set email alerts
|

305. The alkylation of tri- and tetra-alkylpyrroles

Abstract: The action of alkyl iodides on the Grignard derivatives of 2 : 3 : 4-and 2 : 3 : 5-trialkylpyrroles and 2 : 3 : 4 : 5-tetra-alkylpyrroles is shown to give tetra-and penta-alkyl-2H-pyrroles (pyrrolenines) containing 2 : 2-gemdialkyl groups. The reaction is inhibited by the presence of ester substituents on the pyrrole ring.ALTHOUGH the structure of the alkylation products of pyrroles caused a lengthy poleniic some forty years ago, the subject has scarcely received comment since. In spite of all the early work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With more reactive alkylating agents, e.g. (144) Similarly, the corresponding reaction with benzyl chloride yields 2-benzyl-2,5-dimethyl-2//-pyrrole and 3-benzyl-2,5-dimethylpyrrole. (4()3) Alkylation of (H39a) with propargyl bromide and with bromoferrocene also gives C-substituted products.…”
Section: H39amentioning
confidence: 99%
See 1 more Smart Citation
“…With more reactive alkylating agents, e.g. (144) Similarly, the corresponding reaction with benzyl chloride yields 2-benzyl-2,5-dimethyl-2//-pyrrole and 3-benzyl-2,5-dimethylpyrrole. (4()3) Alkylation of (H39a) with propargyl bromide and with bromoferrocene also gives C-substituted products.…”
Section: H39amentioning
confidence: 99%
“…* 385 When the methylation of (H39a) is allowed to proceed to only 10% completion, it is found that the initially formed 2-and 3-methylpyrroles are methylated at the same rate, but that the 2,3-dimethylpyrrole is methylated at the 5-position more rapidly than the methylation of 2,5-dimethylpyrrole at the 3-position. (144,145) Contrary to earlier reports (408) that (H39a) reacts with 4-chlorobutyronitrile to give 2-(2-pyrryl)-l-pyrroline (H43a), it has been established that normal alkylation of the pyrrole ring occurs to give 2-and 3-(3-eyanopropyl)pyrrole in a ratio of 4-4 : l. (399) However, it has also been claimed that equimolar amounts of the nitrile and 2,3,4-trimethylpyrrylmagnesium halides give (H43b), whereas when there is an excess of the nitrile the 2//-pyrrole (H44) is formed. The inductive effect of alkyl groups should make the alkylpyrroles less acidic but the anions should be more nucleophilic than pyrrole.…”
Section: H39amentioning
confidence: 99%
“…The action of alkyl iodides on the Grignard derivatives of 2,3,4-and 2,3,5-trialkylpyrroles and 2,3,4,5tetraalkylpyrroles was shown to afford tetraand pentaalky 1-2,4-pyrroles (pyrrolenines) with 2,2-gemdialkyl groups. This reaction was inhibited by the presence of ester substituents on the pyrrole ring (50).…”
Section: A Alkylationmentioning
confidence: 99%